0058 Associations between socioeconomic status, rurality and motor vehicle traffic crash injury severity and treatment outcomes: findings from the nebraska trauma registry. (26th April 2015) - Cooper, Rachel; Qu, Ming; Lin, Ge
Abstract : Statement of purpose: Based on geocoded data from the Nebraska's trauma registry, the current study examines how socioeconomic status and rurality are associated with MVC injury severity and treatment outcomes. Methods/Approach: Data from 2007–2012 was taken from Nebraska's Trauma Registry. Injuries caused by MVC were identified using ICD-9 External Cause of Injury Codes. 13, 693 cases in the registry met criteria for this study. Cases were geocoded to residential addresses. Poverty status was determined by census tract, and rurality by county. Descriptive and multivariate analyses were used to determine associations between outcome variables, and socioeconomic status (neighbourhood poverty levels) and rurality. Two outcome variables, hospital length of stay and discharge to rehabilitative or homecare services, were considered. Results: Persons from low-income neighbourhoods had a greater rate of inpatient treatment than persons from wealthier neighbourhoods. In particular, single-system or minor injuries (ISS <15) from lower income neighbourhoods were comparatively more likely to be admitted. Persons under 65 years old from low-income neighbourhoods had a significantly longer mean length of stay in the hospital for minor injuries. Persons from rural areas were less likely to be discharged to further services, and moderately more likely to have longer lengths of stay. Conclusions: Persons from low-income neighbourhoods were more likely to be admitted for minor injuries, to remain longer in the hospital and to be discharged without further services. This suggests that this group may lack access to outpatient care to treat minor injuries, or to continue treatment once discharged. The latter may encourage longer stays in hospital to ensure treatment compliance. Lack of access was also apparent for rural patients, who had longer lengths of stay and fewer discharges to further services than their urban counterparts. Significance and contribution to the field: Previous studies examining individual and neighbourhood risk factors of Motor Vehicle Traffic Crashes (MVC) injuries often use data sources where treatment and treatment outcomes were not often considered or reliable. Trauma Registry data provides rich and reliable patient information.